Equine Perineal and Vulvar Conformation Correction Using a Modification of Pouret's Technique - Papa, Frederico Ozanam [UNESP]; Melo, Cely M.; Monteiro, Gabriel A.; Papa, Patricia M.; Guasti, Priscilla N.; Maziero, Rosiara Rosária D.; Derussi, Ana Augusta P.; Magalhães, Luis Carlos O.; Martin, José Carlos; Martin, Ian (Elsevier, 2013)
An incompetent vulvar seal leads to reproductive failure, and a surgical intervention might be required. The present paper describes modifications to Pouret's surgery. We suggest the use of a simple interrupted vertical mattress suture, which avoids seroma. Eighteen Brazilian Jumping Horse mares, older than 20 years and barren for 3-5 consecutive years, underwent modified Pouret's surgery. A horizontal skin incision of 3-4 cm was made half way between the anus and upper commissure of the vulva. The submucosal and connective tissue were dissected, and the rectovaginal shelf was split horizontally by sectioning the muscular and ligamentous connections between the anus, vulva, caudal portion of the rectum, and vagina until the vulva was oriented vertically. The wound was changed from a horizontal plane to a vertical plane by placing the suture vertically using approximately eight interrupted U sutures distributed in two layers with polyamide thread. The modified Pouret's surgical technique provided a perfect coaptation of the vulvar lips and a correct perineal position. Those mares that presented with horizontally tipped vulvar lips due to advanced age and stretching of the pelvic tissues by multiple foaling had their vulvas replaced. Also, the surgical procedure was easy to perform. As to fertility, of the 18 initial mares, 14 were inseminated, and all became pregnant. Thus, it was possible to conclude that the anatomical changes performed throughout the surgical procedure predisposed to a better vulvar coaptation, correcting the pneumovagina. © 2013 Elsevier Inc. All rights reserved.
Keywords: Endometritis; Mares; Pneumovagina; Reproductive failure; Reproductive surgery; Vulvoplasty